2008
DOI: 10.1007/s11119-008-9061-5
|View full text |Cite
|
Sign up to set email alerts
|

An on-farm approach to quantify yield variation and to derive decision rules for site-specific weed management

Abstract: Grain yield often varies within agricultural fields as a result of the variation in soil characteristics, competition from weeds, management practices and their causal interactions. To implement appropriate management decisions, yield variability needs to be explained and quantified. A new experimental design was established and tested in a field experiment to detect yield variation in relation to the variation in soil quality, the heterogeneity of weed distribution and weed control within a field. Weed seedli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 25 publications
1
19
1
1
Order By: Relevance
“…Therefore, even the highest thresholds (treatment 4) are acceptable for site-specific weed control in this case. A similar result was reported also by Ritter et al (2008) who partially explained this by the absence of a negative side effect of the herbicide on the crop. The statistical insignificance was caused by high total variance of the analysed data, suggesting that the grain yield could be affected by other factors.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, even the highest thresholds (treatment 4) are acceptable for site-specific weed control in this case. A similar result was reported also by Ritter et al (2008) who partially explained this by the absence of a negative side effect of the herbicide on the crop. The statistical insignificance was caused by high total variance of the analysed data, suggesting that the grain yield could be affected by other factors.…”
Section: Resultssupporting
confidence: 87%
“…The statistical insignificance was caused by high total variance of the analysed data, suggesting that the grain yield could be affected by other factors. Ritter et al (2008) also mentioned that a high variance of the data can limit the statistical analyses of single effects but that the variance is crucial for the effective utilisation of precision farming techniques.…”
Section: Resultsmentioning
confidence: 99%
“…The yields of all treatments are compared in Figure 5 and the yield map of the entire experimental field is presented in Figure 3. Ritter et al (2008) reported a similar effect of SSWM on crop yield, as site-specific treatments caused no significant decrease of wheat yield compared to the whole-field herbicide application. Other studies (e.g.…”
Section: Methodsmentioning
confidence: 71%
“…Ritter et al 2008). The economic threshold does not, however, take into account weed reproduction and possible changes of weed species populations in subsequent years.…”
mentioning
confidence: 99%
“…Yield and NPP are often satellite driven, recorded and modelled (Smit et al, 2008;Prieto-Blanco et al, 2009;Kurtz et al, 2009). Also, permanent recording of spatial crop yield data as done in precision farming (Ritter et al, 2008;Schellberg et al, 2008;Lukas et al, 2009) may produce databases which have the potential to predict the productivity of land by statistical procedures of spatio-temporal auto-regressive forecasting, state-space approaches (Wendroth et al, 2003) or combinations of models and data (Reuter et al, 2005;Schellberg et al, 2008). The latter approaches developed for precision farming may provide excellent GIS-based modelling or even forecasting of land productivity in the field and at a regional scale but algorithms are rarely transferrable to other regions.…”
Section: Direct Recordings Of Biomass and Crop Yield Datamentioning
confidence: 99%